Do Peatlands in Central Kalimantan Have the Potential for Sustainable Ecotourism Development so That They Can Increase Regional Finan-cial Income? - Irawan Irawan; Wiwin Zakiah; Yudi Pungan; Fujun La (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2022)
The purpose of this study was to identify and analyze the potential and strategy for developing peat areas as sustainable ecotourism objects. The research was conducted using a field explanation to see firsthand the potential of peat areas as ecotourism destinations. Primary data collection was carried out directly by means of interviews and questionnaires to 150 respondents by purposive sampling. Analysis of the data used the Guidelines for Assessment of Tourist Attractions Based on the ADO-ODTWA Guidelines of the Directorate General of PHKA, 2003. Meanwhile, the analysis of ecotourism development strategies for peat areas used SWOT analysis and Process Hierarchy Analysis. The results showed (1) Central Kalimantan peatland area is quite potential to be developed as an ecotourism destination. (2). The development strategy was chosen as a strategy of rapid growth and stable growth to improve the tourist visits to the peatlands, (3) The indicator of the attractiveness of the peatlands of Central Kalimantan as the first rank and the reason for tourists to visit ecotourism in the peatlands.